Dostępność produktów leczniczych w Polsce – ujęcie prawno-ekonomiczne - Żak, Konrad (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The pharmaceutical law system determines the functioning of the market in providing access to medicinal products, which significantly affects the level of health safety of citizens. The specificity of trade in medicinal products forces the detail of legal regulations in relation to the distribution process, hence each country normalizes the market on its own. The nature of national pharmaceutical law systems implies the effectiveness of the system for providing patients with reimbursed medicinal products. The aim of the study is to indicate the impact of changes in the pharmaceutical law system on the national system of supplying medicinal products in the context of the occurrence of illegal export of medicines. The following research methods are being adopted to address the aforementioned issues: a critical analysis of the subject literature and an analysis of legal acts and examination of the related documents. This is to show the scale of illegal drug exports and the impact of re-exports on the level of patient access to medicinal products This will allow conclusions to be drawn regarding the level of effectiveness of the control system operated by the State Pharmaceutical Inspection and will allow the indication of recommendations to optimize the system of supervision over the pharmaceutical market.
Keywords: pharmaceutical market; pharmaceutical law; distribution; pharmacy; medicinal products